2014
DOI: 10.1517/14728214.2015.985203
|View full text |Cite
|
Sign up to set email alerts
|

Emerging drugs for the treatment of cocaine use disorder: a review of neurobiological targets and pharmacotherapy

Abstract: Research into cocaine pharmacotherapy must continue to show innovation. Given that medications targeting single neurotransmitter systems have demonstrated little efficacy in treatment of cocaine use disorder, the recent focus on pharmacotherapeutic agents with multiple neurobiochemical targets represents an exciting shift in trial design and approach. Additionally, consideration of pharmacogenetics may be helpful in identification of subpopulations of cocaine-dependent individuals who may preferentially respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 125 publications
0
33
0
2
Order By: Relevance
“…Although knowledge of reward mechanisms has significantly increased in recent decades, there are currently no approved medications for the treatment of cocaine dependence and behavioural treatment has shown limited efficacy (Shorter et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Although knowledge of reward mechanisms has significantly increased in recent decades, there are currently no approved medications for the treatment of cocaine dependence and behavioural treatment has shown limited efficacy (Shorter et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Given the need for more direct coordination across disciplines in life sciences discovery (e.g., Zerhouni), concerns about the ability of animal models to inform the management of human conditions (e.g., Collins, 2011), and the demand for medications to treat cocaine use disorder (Kampman, 2010; Shorter et al, 2015), the goal of this and the companion study described in this issue (Johnson et al, 2016) was to back-translate a drug versus non-drug choice procedure in humans to rhesus monkeys, in order to establish a pipeline for cocaine use disorder medications development. These parallel studies demonstrated similar patterns of choice for cocaine and a non-drug alternative reinforcer under matching self-administration schedules and experimental session conditions in humans and rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Despite intense efforts, an effective and acceptable medication for treating cocaine use disorder has yet to be identified (Kampman, 2010; Shorter et al, 2015). A recent review of the literature revealed that, of the more than 60 medications evaluated in randomized controlled clinical trials for cocaine use disorder, only 10 had also been screened using both animal and human laboratory self-administration procedures (Czoty et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidity with other psychiatric conditions, including depression and anxiety disorders, is commonly seen in substance use disorders, including cocaine abuse (Volkow, 2004;Vorspan et al, 2015). Pharmacotherapies developed for treating cocaine abuse have been largely unsuccessful (Shorter et al, 2015) and some purported treatment mechanisms elicit or exacerbate unwanted symptoms (eg, depression, anxiety, increased impulsivity, cognitive impairments, or psychosis) (Homayoun et al, 2004;Kishi et al, 2013;Moore et al, 2014). Developing pharmacotherapies targeting cocaine addiction and associated comorbidities while lacking adverse effects may provide greater therapeutic efficacy as well as medication compliance, increased abstinence rates and improved overall treatment success.…”
Section: Introductionmentioning
confidence: 99%